1989
DOI: 10.1289/ehp.8981139
|View full text |Cite
|
Sign up to set email alerts
|

Sun exposure and malignant melanoma among susceptible individuals.

Abstract: The purpose of this case-control study was to identify susceptible subgroups, primarily based on pigmentary characteristics, at higher risk of developing melanoma when exposed to the sun. The study group, which was interviewed from 1979 to 1982, consisted of 289 consecutive patients with melanoma and 527 randomly selected controls without cancer. In general, the risk of melanoma associated with sun exposure was greater for individuals expected to be susceptible on the basis of poor ability to tan, but not othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…It is unlikely that our findings could be attributable to greater misclassification of L* among subjects with low total sun exposure, since results were similar for L* and MED and measurements were made on the buttock, an area that is not affected by sun exposure. In addition, these findings are in agreement with those of other case-control studies (63)(64)(65)(66)(67)(68) that measured sun exposure and sun sensitivity in a number of different ways. This suggests that skin sensitivity in the presence of sun exposure is an important risk factor for CMM and that reduction of sun exposure could be especially beneficial for ultraviolet-sensitive persons.…”
Section: Discussionsupporting
confidence: 90%
“…It is unlikely that our findings could be attributable to greater misclassification of L* among subjects with low total sun exposure, since results were similar for L* and MED and measurements were made on the buttock, an area that is not affected by sun exposure. In addition, these findings are in agreement with those of other case-control studies (63)(64)(65)(66)(67)(68) that measured sun exposure and sun sensitivity in a number of different ways. This suggests that skin sensitivity in the presence of sun exposure is an important risk factor for CMM and that reduction of sun exposure could be especially beneficial for ultraviolet-sensitive persons.…”
Section: Discussionsupporting
confidence: 90%
“…Both Weinstock et al (7 tive individuals. This modification of the and Dubin et al (8) found higher risks of melanoma risk by the ability to tan and the melanoma among sun-sensitive persons opportunity for gradual tanning has only than among more sun-resistant persons. been addressed in a few studies (2,3,7,8).…”
Section: Discussion Evidence Of An Association With Melanomamentioning
confidence: 91%
“…Sun sensitivity characteristics are widely accepted as risk factors for CM, including eye, hair and skin color, tendency to sunburn and inability to tan (20, 76, 86). Lighter complexion as measured by both Fitzpatrick skin-type (21, 33, 41) and self-reported skin color (fair, medium, or dark) (8789) appear to be the most consistent risk factors for CM.…”
Section: Discussionmentioning
confidence: 99%